Natural Radioactivity in Groundwater and Its Associated Cancer Risk Due To Ingestion of Water from Gambella Town, Ethiopia - Goshu, Belay Sitotaw; Merga, Bikila; Cheru, Nega (Budapest International Research in Exact Sciences (BirEx) Journal, 2025)
Radionuclides, both natural and man-made, are the primary causes of human radiation exposure. These radionuclides can dissolve in water, enter the body via drinking water, and harm human health. In this study, five samples were collected from the groundwater resources of Gambella town. The specific activities of 226Ra, 232Th, and 40K were determined in the samples using gamma-ray spectrometry and a high-purity germanium (HPGe) detector. The fatality cancer risk (FCR), lifetime fatality cancer risk (LFC), severe hereditary effects (SHE), and estimated lifetime hereditary effects (ELHE) in diverse samples. The findings show significant differences in FCR and LFC, implying that certain populations are more likely to get cancer. The SHE values, while lower, show the possibility of genetic consequences. ELHE ideals stress the need to address potential genetic repercussions in the long run. These findings are consistent with previous research, stressing the importance of continued monitoring and public health initiatives to reduce the dangers associated with radiation exposure. The study emphasizes the necessity of protection measures for vulnerable populations and ensuring long-term health results.